Penerapan Marketing Mix Dan Digital Marketing Pada Usaha Gula Merah Produksi Desa Dawan Klod - Martauli Rezki Munthe; Putu Purnama Dewi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
ABSTRACT The lack of marketing for MSME products is a problem that gets little attention, one of which is the brown sugar produced by Dawan Klod Village. The entrepreneurs still do market activity conventionally and don’t understand the marketing strategy for selling their brown sugar. Therefore, the purpose of community service activities is to provide a solution to this problem by providing education to local brown sugar entrepreneur regarding marketing strategies, that are marketing mix and digital marketing. The work program is carried out by presenting materials related to the introduction of product innovation and packaging of brown sugar, examples of implementing marketing mixes for brown sugar product, branding video and photos as content to be published and optimizing social media and e-commerce as part of implementing digital marketing. The result of the program that have been implemented is brown sugar entrepreneur gaining new understanding and implementing it directly. Apart from that, it has also succeeded in giving awareness that’s important to apply a marketing mix and digital marketing in order to increase the selling power of brown sugar and their income. In the future, it’s also hope that brown sugar entrepreneur will be able to expand their market and maintain their business in the midst of the current digitalization era. Keywords: Marketing Strategy, Marketing Mix, Digital Marketing, Social Media, E-Commerce